Pediatric Telehealth Expansion in Response to COVID-19 - Williams, Stormee; Hill, Kristina; Xie, Luyu; Mathew, M. Sunil; Ofori, Ashley; Perry, Tamara; Wesley, Danielle; Messiah, Sarah E. (Frontiers in Pediatrics, 2021)
Introduction: Telehealth utilization has been steadily increasing for the past two decades and has been recognized for its ability to access rural and underserved populations. The advent of COVID-19 in March 2020 limited the feasibility of in-person healthcare visits which in turn increased telehealth demand and use. However, the long-term impacts of COVID-19 on the telehealth sector of the healthcare industry, and particularly on pediatric healthcare volume demand and subsequent expansion, are yet to be determined. Objective and Methods: To understand the impact of COVID-19 on telehealth utilization, volume demand, and expansion in one large pediatric healthcare system serving greater Dallas-Fort Worth, Texas, data on telehealth clinic visits by month, pre-COVID and post/current-COVID were compared. A quasi-experimental pretest-posttest design analysis compared telehealth visit counts from 54 ambulatory pediatric health specialties. Pre-post new patient counts were also analyzed via chi square. Results: Total telehealth visit counts significantly increased between March–October 2019 (2,033 visits) compared to March-October 2020 (54,276 visits). Mean monthly telehealth visits increased by 6,530 visits, or 2,569.75% over the same time period (p < 0.0001). In October 2020, total telehealth visits were still 1,194.78% above 2019 levels (345 visits in 2019 vs. 4467 visits in 2020). Discussion: Results here show a substantial volume increase in telehealth-delivered pediatric healthcare and resource utilization as a response to COVID-19. This provides a template for permanent adoption of pediatric telehealth delivery post pandemic. Further investigation is needed to determine impacts upon resource allocation, processes, and general models and standard of care to assist facilities and programs to better address the needs of the pediatric populations they serve in the post-COVID era.